The Protective Effects of Inulin-Type Fructans Against High-Fat/Sucrose Diet-Induced Gestational Diabetes Mice in Association With Gut Microbiota Regulation - Miao, Miao; Wang, Qing; Wang, Xinyan; Fan, Chong; Luan, Ting; Yan, Lina; Zhang, Yue; Zeng, Xin; Dai, Yongmei; Li, Ping (Frontiers in Microbiology, 2022)
Background: Inulin-type fructans (ITF) have been used as prebiotics to alleviate glucose and lipid metabolism disorders. However, few studies evaluated the microbial mechanism of ITF in improving maternal metabolic status during pregnancy. Methods: C57BL/6J mice were fed a high-fat/sucrose diet (HFD) for 4 weeks before and throughout pregnancy to induce a model of Gestational diabetes mellitus (GDM). Body weight, glycolipid metabolic parameters and fecal short chain fat acids (SCFAs) were assessed in the experimental process. The effects of ITF on the fecal microbiota were performed by 16S rRNA gene amplicon sequencing. Results: Pregnant HFD-fed mice displayed significant insulin resistance and dyslipidemia. ITF (3.33g/kg/d) treatment improved glucose and lipid metabolism disorder parameters in HFD induced GDM mice, alleviated fat accumulation and glucose intolerance. The α diversity of gut microbial community was increased in ITF mice, while the β diversity returned to the level of normal chow diet (NCD) mice. Interestingly, Verrucomicrobia, Bifidobacterium and Akkermansia were obviously enriched, while Dubosiella was obviously lessened after inulin treatment. Further analysis indicated that Dubosiella was positively correlated with markers of glycolipid metabolism disorders, whereas the ITF-supplemented diet partially reversed the changes. Conclusions: Our results suggest that the ITF treatment may alleviate glucose and lipid metabolism disorders with the mediation of gut microbiota.